Depression and Self-Efficacy Among Iranian Children During the Prevalence of COVID-19 Disease - Zakeri, Mohammad Ali; Dakkalirad, Abdollah; Saedi, Fahimeh; Shahnavazi, Allahyar; Kordi, Mehri; Ahmadipour, Maryam; Dehghan, Mahlagha (Frontiers in Pediatrics, 2022)
The coronavirus disease 2019 (COVID-19) outbreak has quickly endangered the physical and mental health of people in the community, particularly vulnerable people such as children. This study was carried out to investigate the depression and self-efficacy of Iranian children during the COVID-19 outbreak. This cross-sectional research was conducted on 321 students aged 8 to 17 in southeast Iran. A social media-based online questionnaire was used to collect data. The information was gathered using demographic and COVID-related items, the Children's Depression Inventory (CDI), and the Self-Efficacy Questionnaire for Children (SEQ-C). No significant correlation was observed between depression and self-efficacy of children (P = 0.23). However, in subscale of CDI, negative mood, ineffectiveness and negative self-esteem had a significant correlation with self-efficacy (<0.001). Depression had a significant correlation with family income (p = 0.017), being at risk of coronavirus infection (p = 0.036), effectiveness of preventive measures (p = 0.015) and how information about the coronavirus disease was obtained (p = 0.018). According to the results, the mean score of depression was higher than the midpoint of the questionnaire in Iranian children, therefore, it is needed to take the necessary measures and treatment plans to reduce the rate of depression in children. Further research is needed to assess and prevent childhood depression.